2022
DOI: 10.1002/essoar.10512706.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When record breaking heat waves should not surprise: skewness, heavy tails and implications for risk assessment

Abstract: Extreme heat waves beset western North America during 2021, including a 46.7°C (116°F) observation in Portland, Oregon, an astonishing 5°C above the previous record. Using Portland as an example we provide evidence for a latent risk of extreme heat waves in the Pacific Northwest (PNW) and along the west coast of the United States where a maritime climate and its intrinsic variations yield a positive skewness in summertime daily maximum temperatures. A generalized Pareto extreme value analysis yields a heavy ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…As discussed in Section 3.1, local temperatures exhibit well‐known and notable departures from the normal distribution on the extremes of frequency distributions (e.g., Bjarke et al., 2022; Huybers et al., 2014; Lewis & King, 2017; Loikith & Neelin, 2015; McKinnon & Simpson, 2022; Ruff & Neelin, 2012; Sardeshmukh et al., 2015; Schär et al., 2004; Sippel et al., 2015; Sura, 2011; Sura & Perron, 2010; Tamarin‐Brodsky et al., 2020). In the discussion of Figure 2a, we showed that the shapes of the temperature distributions significantly increase the incidence of heat events on the local scale ; in Figure 2b, we consider their effects on the hemispheric scale : For a given skewness and kurtosis, we generate 100 random time series (roughly the effective number of spatial degrees of freedom in the data) sampled from a Pearson distribution, and calculate the percent of days on which any of the random time series exceeds +4s.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…As discussed in Section 3.1, local temperatures exhibit well‐known and notable departures from the normal distribution on the extremes of frequency distributions (e.g., Bjarke et al., 2022; Huybers et al., 2014; Lewis & King, 2017; Loikith & Neelin, 2015; McKinnon & Simpson, 2022; Ruff & Neelin, 2012; Sardeshmukh et al., 2015; Schär et al., 2004; Sippel et al., 2015; Sura, 2011; Sura & Perron, 2010; Tamarin‐Brodsky et al., 2020). In the discussion of Figure 2a, we showed that the shapes of the temperature distributions significantly increase the incidence of heat events on the local scale ; in Figure 2b, we consider their effects on the hemispheric scale : For a given skewness and kurtosis, we generate 100 random time series (roughly the effective number of spatial degrees of freedom in the data) sampled from a Pearson distribution, and calculate the percent of days on which any of the random time series exceeds +4s.…”
Section: Resultsmentioning
confidence: 98%
“…The long‐term mean of all three indices is comparable to that in Figures 3a–3c, but the long‐term trends in all three indices are no longer significant. Hence, while changes in temperature variability and skewness may play a role in changes in extreme temperature anomalies over certain locations (Bjarke et al., 2022; Lewis & King, 2017; McKinnon & Simpson, 2022; McKinnon et al., 2016; Sardeshmukh et al., 2015; Schär et al., 2004; Schneider et al., 2015; Sippel et al., 2015; Tamarin‐Brodsky et al., 2020), changes in mean temperature clearly account for the preponderance of the hemispherically integrated changes in heat events (e.g., Amaya et al., 2023; Donat & Alexander, 2012; Hansen et al., 2012; Oliver et al., 2018; Rhines & Huybers, 2013; Seneviratne et al., 2021; Simolo et al., 2011; Thompson et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorrectly applying Gaussian data assimilation in these cases can introduce biases in the forecast, or even predict values outside the physical bounds. Moreover, this assumption can have impacts on unbounded variables; for example, the likelihood of extreme events, such as heat waves, can be severely underestimated when assuming Gaussian statistics for the temperature (Bjarke et al, 2022;Sardeshmukh et al, 2015). Sophisticated techniques have been developed to deal with non-Gaussian errors, based largely on particle filters (van Leeuwen, 2009;van Leeuwen et al, 2019).…”
mentioning
confidence: 99%